Política fiscal no Brasil: uma estimativa dos multiplicadores fiscais para o período 1997-2018 - Alves, Vinícius de Oliveira (Universidade Federal de São Carlos, 2020)
This dissertation aims to evaluate the capacity of fiscal policy to smooth the cyclical fluctuations of the Brazilian economy. A theoretical discussion is held regarding the possibility of stabilizing the level of activity through public spending and / or through changes in taxation, highlighting the differences between the conventional and the Keynesian view. Subsequently, an assessment of the fiscal policy guidelines in Brazil between 1995 and 2018 is made in order to provide historical and institutional elements for empirical analysis. From the calculation of fiscal multipliers for various components of primary expenditure and for net primary revenue, the empirical investigation admits as general hypothesis that the responses of the aggregate product to the shocks in the various fiscal variables differ between the recessive and expansive phases of the Brazilian economic cycle during the period 1997-2018. Two models are estimated: a structural VAR of the linear type and a non-linear VAR with regime change from the Markov-Switching process. In a second step, Public Sector Net Debt is included in both models to verify whether public debt overestimates fiscal multipliers. Public debt is not a predominant variable for the magnitude of the fiscal multiplier, as part of the literature suggests, as the economic cycle prevails over the size of the fiscal shock. In general, there are two contributions to the debate and to empirical research. The first is the estimation of fiscal multipliers for the Brazilian economy in a non-linear model with public debt. The second is the discussion of the results in the light of the economic policy actions of all governments in the period studied, relating them to the historical evolution of macroeconomic thinking on fiscal policy.
Fiscal policy in Brazil: an estimate of fiscal multipliers for the period 1997-2018
Keywords: Política fiscal; Multiplicadores fiscais; Abordagens VAR; Ciclo econômico; Política anticíclica; Fiscal policy; Tax multipliers; VAR approaches; Economic cycle; Anti-cyclical policy; CIENCIAS SOCIAIS APLICADAS::ECONOMIA::ECONOMIA MONETARIA E FISCAL::POLITICA FISCAL DO BRASIL